The health burden of pollution: the impact of prenatal exposure to air pollutants - Vieira, Sandra E (Int J Chron Obstruct Pulmon Dis, 2015)
Exposure to atmospheric pollutants in both open and closed environments is a major cause of morbidity and mortality that may be both controlled and minimized. Despite growing evidence, several controversies and disagreements exist among the studies that have analyzed the effects of prenatal pollutant exposure. This review article aims to analyze primary scientific evidence of the effects of air pollution during pregnancy and the impact of these effects on the fetus, infant health, and in particular, the respiratory system. We performed a review of articles from the PubMed and Web of Science databases that were published in English within the past 5 years, particularly those related to birth cohorts that began in pregnancy with follow-up until the first years of life. The largest reported effects are associated with prenatal exposure to particulate matter, nitrogen dioxide, and tobacco smoke. The primary effects affect birth weight and other parameters of fetal biometry. There is strong evidence regarding the impact of pollutants on morbidity secondary to respiratory problems. Growing evidence links maternal smoking to childhood asthma and wheezing. The role of passive maternal smoking is less clear. Great heterogeneity exists among studies. There is a need for additional studies on birth cohorts to monitor the relationship between the exposure of pregnant women to pollutants and their children’s progress during the first years of life.